Intertemporal social choice and climate stabilization. (29th October 2004) - Howarth, Richard B.
This paper examines the implications of alternative approaches to intertemporal social choice in a numerically calibrated model of interactions between global climate change and the world economy. Under cost-benefit analysis, relatively modest steps towards greenhouse gas emissions abatement are justified as economically efficient. Under classical utilitarianism and the precautionary principle, in contrast, aggressive steps towards climate stabilization emerge as socially optimal. The paper reviews the value judgements that support each of these normative approaches, arguing that the precautionary principle is most closely tied to the goals and objectives of the Framework Convention on Climate Change.